2015
DOI: 10.1002/term.2002
|View full text |Cite
|
Sign up to set email alerts
|

In vivobiocompatibility assessment of poly (ether imide) electrospun scaffolds

Abstract: Poly(ether imide) (PEI), which can be chemically functionalized with biologically active ligands, has emerged as a potential biomaterial for medical implants. Electrospun PEI scaffolds have shown advantageous properties, such as enhanced endothelial cell adherence, proliferation and low platelet adhesion in in vitro experiments. In this study, the in vivo behaviour of electrospun PEI scaffolds and PEI films was examined in a murine subcutaneous implantation model. Electrospun PEI scaffolds and films were surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…35,36 During the foreign body response, monocytes and macrophages are activated, which leads to collagen matrix deposition and angiogenesis. [35][36][37][38][39] Similar studies have concluded that when macrophages are activated by a foreign material surface, they produce a greater number of vessels and angiogenic factors such as MMP-9, TIMP-1, and TIMP-2. [38][39][40][41] Moreover, cell infiltration is a critical process in promoting tissue integration between implanted material and host tissue.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…35,36 During the foreign body response, monocytes and macrophages are activated, which leads to collagen matrix deposition and angiogenesis. [35][36][37][38][39] Similar studies have concluded that when macrophages are activated by a foreign material surface, they produce a greater number of vessels and angiogenic factors such as MMP-9, TIMP-1, and TIMP-2. [38][39][40][41] Moreover, cell infiltration is a critical process in promoting tissue integration between implanted material and host tissue.…”
Section: Discussionmentioning
confidence: 74%
“…[35][36][37][38][39] Similar studies have concluded that when macrophages are activated by a foreign material surface, they produce a greater number of vessels and angiogenic factors such as MMP-9, TIMP-1, and TIMP-2. [38][39][40][41] Moreover, cell infiltration is a critical process in promoting tissue integration between implanted material and host tissue. [42][43][44] The presence of a thick fibrous capsule could potentially be inhibiting these processes that allow for successful implant and host integration.…”
Section: Discussionmentioning
confidence: 74%
“…As such, the porous structure of scaffolds facilitates vascularization, and the collagen scaffolds are biocompatible when implanted in vivo in small animals. The murine subcutaneous implant model is often used to study the biocompatibility of scaffolds [ 27 ] as well as angiogenesis during wound healing [ 28 ]. An infiltration of host cells into the collagen scaffolds was seen at week 1 and an accumulation of host cells at the central region occurred from week 2.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory response and capsule formation seem also to depend on the shape of the implant. Capsule thickness and inflammatory infiltration cells significantly decreased for scaffolds during days 7–28, while remaining unchanged for films produced from the same polymer . In addition, experimental prevention of integrin binding of PMN and incubation of PMN with hydrophobic polymers in a protein‐free setting is not completely abolishing acute inflammation .…”
Section: Phase 2: Acute Inflammation (Mast Cells and Granulocytes)mentioning
confidence: 96%